Safety and Immunogenicity of a Modified Self-Amplifying Ribonucleic Acid (saRNA) Vaccine Encoding SARS-CoV-2 Spike Glycoprotein in SARS-CoV-2 Seronegative and Seropositive Ugandan Individuals - Jonathan Kitonsa; Jennifer Serwanga; Hannah M. Cheeseman; Andrew Abaasa; Jane Frances Lunkuse; Eugene Ruzagira; Laban Kato; Florence Nambaziira; Gerald Kevin Oluka; Ben Gombe; Sembera Jackson; Joseph Katende Ssebwana; et al. (Vaccines, 2025)
Background: The COVID-19 pandemic highlighted the need for innovative vaccine platforms that elicit durable immunity. Self-amplifying RNA (saRNA) vaccines offer rapid production and dose-sparing advantages over traditional mRNA platforms. In Uganda’s first SARS-CoV-2 vaccine trial (NCT04934111), we assessed the safety and immunogenicity of a saRNA vaccine encoding the SARS-CoV-2 spike (S) glycoprotein in seronegative and seropositive adults. Methods: This non-randomised phase 1 trial (December 2021–April 2022) enrolled 42 healthy adults (18–45 years), including 12 seronegative and 30 seropositive for SARS-CoV-2. Participants received two 5 μg doses of saRNA vaccine, four weeks apart. Reactogenicity was assessed using diary cards for seven days post-vaccination, and adverse events were monitored throughout the 24-week study. Binding and neutralising antibody levels were quantified using ELISA and pseudovirus neutralisation assays. Findings: The vaccine was well tolerated, with only mild-to-moderate adverse events, including fatigue, headache, and chills. No serious vaccine-related events occurred. Among seronegative participants, 91.6% seroconverted after two doses (median S-IgG: 3695 ng/mL, p < 0.001). In the seropositive participants, S-IgG rose modestly from 7496 to 11,028 ng/mL after the second dose. Neutralising titres increased modestly across WT, BA.2, and A.23.1 variants, with no significant differences between groups. Conclusion: The saRNA SARS-CoV-2 vaccine was safe and immunogenic, inducing robust spike glycoprotein-specific antibody responses, particularly in seronegative participants. This trial demonstrates the potential of saRNA vaccines for broader use.